مبهمات القرآن الكريم في كتابات المستشرقين ـ دراسة تحليلية نقدية ـ - غطاس, محمد (جامعة الوادي university of eloued, 2023)
"هذا البحث بعنوان: مبهمات القرآن الكريم في كتابات المستشرقين ـ دراسة تحليلية نقدية ـ. وتهدف هذه الدراسة إلى تسليط الضوء على مثارات الجدل والتشكيك التي نادى بها المستشرقون قديما وحديثا حول مبهمات القرآن الكريم في صورتها العامة والخاصة، وذلك من خلال الإجابة عن إشكال رئيس مفاده: ماهي أهم الشبهات التي أثارها المستشرقون حول مبهمات القرآن الكريم ؟ وللإجابة على ذلك فقد انتظمت خطة البحث في ثلاث مباحث، كان أولها للحديث عن مفهوم الإستشراق وأهدافه؛ أما الثاني فقد بُسط فيه القول عن مبهمات القرآن الكريم من جهة الماهية وكذا الأنواع، أما المبحث الثالث فهو صلب الدراسة، وفيه تم عرض أبرز الشبهات مع شيء من التحليل والبيان عن طريق ذكر جملة من الأمثلة التطبيقية التي توضح ذلك. وقد خَلُصت الدراسة إلى نتائج عدة أبرزها أنّ لغة القرآن الكريم وبيئة نزوله قد شكلت عقبة كؤودا وبيئة ضحلة حالت دون وصولهم للفهم السليم لآي التنزيل فضلا عن الجانب القدسي فيه "Praise be to Allah, the Lord of all worlds, and peace and blessings be upon our Prophet Muhammad, his family, and his companions. After this, the research presents a study entitled "Ambiguities of the Noble Quran in Orientalist Writings - A Critical Analytical Study." The objective of this study is to shed light on the controversies and skepticism propagated by Orientalists, both historically and in contemporary times, concerning the ambiguities present in the Noble Quran, both in its general and specific aspects. The primary inquiry addressed is: What are the key doubts raised by Orientalists regarding the ambiguities of the Noble Quran, and what are their implications? To address this query, the research is organized into three sections. The first section discusses the concept and objectives of Orientalism. The second section comprehensively explores the ambiguities of the Noble Quran, encompassing their essence and various types. The third section forms the crux of the study, presenting the most prominent doubts and providing analysis and elucidation through illustrative examples. The study concludes with several significant findings, including the fact that the language of the Noble Quran and the context of its revelation posed as obstacles and superficial surroundings that impeded Orientalists from attaining a sound comprehension of its divine revelation, in addition to its sacred dimension.
تفسير
Keywords: المبهمات.المستشرقين. الشبهات; The vague ones. The orientalists. suspicions